Subdural Empyema in Bacterial Meningitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Researchers at the University of Amsterdam, the Netherlands, evaluated the occurrence, treatment, and outcome of subdural empyema as a complication of community-acquired bacterial meningitis in 28 (2.7%) adults.